PENGEMBANGAN MEDIA PAPAN “PREDIKSI PENUH BUKTI” UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA - Moch Chabib Dwi Kurniawan (Jurnal Didaktika Pendidikan Dasar, 2019)
The square root formula is one of the subjects taught to students in 4th grade of SDN Sentul 1 Tambelang. This subject is considered difficult by the students as it is related to the area of shapes and the square root numbers. Many 4th-grade students find difficulty in calculating the area of a shape based on the formula of the square root. This research was conducted to improve the students’ motivation and their Mathematics learning outcomes, especially on square root numbers by using “Papan Prediksi Penuh Bukti” (Prediction Board of Complete Evidence) media. The development research is carried out in this research to solve problems in classroom learning, particularly in helping students to find the square root numbers easily and quickly. Based on the results of using “Papan Prediksi Penuh Bukti” in the class, it is considered effective and successful. The result of observation showed that students seemed enthusiastic and active while using “Papan Prediksi Penuh Bukti” media in learning the square root formula. In addition, 95% of students like to use this media in the learning process. The students’ assessment also showed a significant increase in their pretest results, that is 19 children were able to complete their learning (95%). Thus, it can be said that learning mathematics by using “Papan Prediksi Penuh Bukti” media can increase students’ motivation and their learning outcomes in Mathematics, especially in the square root numbers.